Transformação digital no contexto organizacional dos órgãos da administração pública direta da prefeitura de São Paulo - Carvalho, Filipe Pereira Nunes de (2024)
Governments from various nations around the world have turned to Digital Transformation (DT) as a means to achieve better performance in the delivery of public services. Properly outlining a planned strategy for DT can efficiently promote the digitalization of services. The objective of this research is to identify the current state of the processes inherent to DT within the organizational context of the direct public administration bodies of the São Paulo City Hall, based on the evaluation of dimensions and their respective key processes for digitalization in organizations as developed by Gökalp and Martinez (2022). This model considers strategic governance, information and communication technology, business process digitalization, and workforce management as essential elements for the success of DT. Additionally, the research aims to propose improvement suggestions and necessary actions for the evolution of DT at the São Paulo City Hall. To achieve this, an exploratory-descriptive research was conducted, employing both qualitative and quantitative methods. A questionnaire was administered to public employees from various departments and sub-municipalities of the São Paulo City Hall, containing questions about the execution of processes considered sufficient and necessary for DT. Furthermore, a semi-structured interview guide was applied to the planning and organizational development analysts - IT discipline - of the São Paulo City Hall. The results indicate that DT is in the execution phase, as three out of the four analyzed key process dimensions were diagnosed as such, namely: i) Information and Communication Technology Management was diagnosed as initiated but still in the planning phase (eight out of ten key processes); ii) Business Process Digitalization was also diagnosed as initiated but still in the planning phase (five out of eight key processes); iii) Workforce Management is initiated but still in the planning phase (three out of four key processes). The results of this research contribute to outlining a holistic and realistic picture of the current state of the key processes supporting the digitalization of services provided by the São Paulo municipal government. It also contributes by establishing a set of improvement suggestions and actions that assist in the evolution of DT for better service delivery to citizens. In this sense, the contributions of this research can serve as a basis for the development of strategies and action plans that can foster the structured and rationalized digital empowerment of São Paulo in the coming years.